Suplementación de L-metionina y estimación dietaria óptima de metionina más cisteína en patos Muscovy en crecimiento (Cairina moschata Linnaeus, 1758) - Pujada A., Hilario (2024)
The aim of the study was to evaluate the effect of dietary supplementation of five levels of L-Met on the productive performance of growing Muscovy male ducks. Methionine supplementation contained 99% L-Met. Seventy-two ducks (0.66 ± 0.11 kg) of 22 days of age were used and randomly distributed into 5 treatments: 1) basal diet (BD) containing 0.5% Met + Cyst, without L-Met supplementation, 2) DB + 0.1% L-Met, 3) DB + 0.2% L-Met, 4) DB + 0.3% L-Met and 5) DB + 0.4% L-Met. Each replicate consisted of three birds. Statistical differences were found for feed intake (p=0.002) and fourth primary feather length (p<0.001), but no significant difference for body weight, total weight gain and feed conversion (p>0.05). Supplementation with 0.1-0.3% L-Met improved feed intake and feather length, with a tendency to improve body weight. Supplementation with 0.4% L-Met decreased feed intake. The concentration of methionine plus cysteine to achieve optimal body weight and feather length was estimated at 0.67 and 0.68%, respectively.